Fabrication, and structural instability of a van-der-Waals Fe\(_5\)GeTe\(_2\) ferromagnet - Phan, The-Long; Nguyen, T. H.; Phuc, H. T.; Dang, N. T.; Thang, P. D.; Tiep, N. H.; Nhat, H. N. (Communications in Physics, 2025)
This work presents the solid-state reaction method used to fabricate a polycrystalline Fe5GeTe2 (FGT) sample, in which chemical reactions of precursors took place at 1000 oC in a sealed evacuated quartz ampoule. X-ray diffraction analyses indicate the monophase in the rhombohedral Rm structure of the as-prepared FGT. Unlike ZnO and spinel ferrites, FGT is unstable and easy to decompose to constitute Fe-, Te- and Ge-related secondary materials by high-energy ball milling for a short time. Furthermore, the storage of FGT under normal atmospheric conditions for a period also leads to its decomposition. Such decompositions would directly influence the magnetic behaviors of FGT. This would limit its application potential in next-generation electronic and spintronic devices.